Jute Fiber Gradation by Grey Fuzzy Logic Approach - Ashis Mitra (Journal of Natural Fibers, 2022)
Jute fiber has a great role in Indian economy. Since, jute fiber quality varies one place to another owing to various reasons, it becomes imperative to go for classification and gradation of jute fibers on the basis of which jute pricing is fixed. Traditionally, jute grading is done by ‘Hand & Eye’ method which is totally subjective. In modern BIS system, a more scientific approach is practised for grading the jute fibers based on six physical fiber parameters like strength, defect, root content, color, fineness, and bulk density. However, color and density parameters are still assessed subjectively. In this paper, a grey fuzzy logic-based MCDM approach has been proposed for ranking/gradation of nine jute fiber samples based on six apposite selection criteria like fiber strength, root content, fiber defects, fiber color, bulk density and fiber fineness. Fuzzy logic has been integrated with grey relational analysis (GRA) to minimize vagueness or imprecision inherent in GRA. The proposed approach closely matches with the ranking patterns attained by the existing BIS system and that by MAHP approach done by an earlier researcher.